Citizenship education in the Covid-19 era: How to become a digital citizen? - Abdul Azis; Maftuhin Maftuhin; Dadi Mulyadi Nugraha (Universitas Negeri Yogyakarta, 2021)
Online learning that is applied to the Citizenship Education course as a result of the Covid-19 pandemic presents quite a challenge for the character development of students. With this, of course, raises a question, how can student character development be carried out only through online learning? By using the Research and Development (R&D) research design, this study seeks to reveal an effort to develop student character so that they can become digital citizens in the midst of the Covid-19 virus pandemic through Citizenship Education learning. The results show that the development of student character through the application of the concept of digital citizenship in online learning of the student-centered Citizenship Education course can be carried out effectively. This is because learning Citizenship Education which is implemented effectively is able to direct students to think critically about contextual problems that occur, so that students can show their character as digital citizens by instilling basic religious and cultural values in applying and mastering science and technology and the arts. with great responsibility.